2021
DOI: 10.3390/metabo12010016
|View full text |Cite
|
Sign up to set email alerts
|

Forming 4-Methylcatechol as the Dominant Bioavailable Metabolite of Intraruminal Rutin Inhibits p-Cresol Production in Dairy Cows

Abstract: Rutin, a natural flavonol glycoside, elicits its diverse health-promoting effects from the bioactivities of quercetin, its aglycone. While widely distributed in the vegetables and fruits of human diet, rutin is either absent or inadequate in common animal feed ingredients. Rutin has been supplemented to dairy cows for performance enhancement, but its metabolic fate in vivo has not been determined. In this study, plasma, urine, and rumen fluid samples were collected before and after the intraruminal dosing of 1… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 6 publications
(2 citation statements)
references
References 48 publications
(63 reference statements)
0
2
0
Order By: Relevance
“…It has been shown that the supplementation of Lactobacillus strains decreased the excretion of urinary p-cresol sulfate in healthy women [20]. Besides microbial interventions, chemical intervention of p-cresol biogenesis could also be achieved as shown in our recent studies, in which microbial AAA degradation, including 4HPAA decarboxylase-catalyzed p-cresol production, was competitively inhibited by green tea polyphenol intake in humans [21] and rutin feeding in dairy cows [22]. Therefore, profiling p-cresol and other AAA degradation products in urine and feces can serve as an effective analytical approach to determine the status of microbial AAA metabolism and its sensitivity to microbial and chemical interventions.…”
Section: Sensitivity Of P-cresol and Paa Biogenesis To Microbial And ...mentioning
confidence: 90%
“…It has been shown that the supplementation of Lactobacillus strains decreased the excretion of urinary p-cresol sulfate in healthy women [20]. Besides microbial interventions, chemical intervention of p-cresol biogenesis could also be achieved as shown in our recent studies, in which microbial AAA degradation, including 4HPAA decarboxylase-catalyzed p-cresol production, was competitively inhibited by green tea polyphenol intake in humans [21] and rutin feeding in dairy cows [22]. Therefore, profiling p-cresol and other AAA degradation products in urine and feces can serve as an effective analytical approach to determine the status of microbial AAA metabolism and its sensitivity to microbial and chemical interventions.…”
Section: Sensitivity Of P-cresol and Paa Biogenesis To Microbial And ...mentioning
confidence: 90%
“…The rupture of the flavonol skeleton is completely afforded by gut bacteria, while subsequent phase II conjugation is primarily catalyzed by mammalian enzymes. Hydrogenation, hydroxylation, and side chain shortening can be mediated by both mammalian and microbial enzymes, whereas dehydroxylation and demethoxylation almost fully result from microbiota. , Taking quercetin as an example, ring fission of the skeleton yielded 3,4-dihydroxyphenylpropionic acid (3,4-DHPPA) and 1,3,5-trihydroxybenzene (phloroglucinol); the former was further catabolized to produce 3,4-dihydroxyphenylacetic acid (3,4-DHPAA), an important metabolite of quercetin. , Furthermore, 3,4-DHPAA was degraded into multiple aromatic catabolites via dihydroxylation, decarboxylation, methylation, and shortening of the side chain . Three phenolic acids, i.e., 3,4-DHPAA, 3-methoxy-4-hydroxyphenylacetic acid (homovanillic acid, HVA), and 3-hydroxyphenylacetic acid (3-HPAA), were identified as major catabolites in the urine of healthy subjects, contributing to 22% of rutin intake. , Additionally, 4-hydroxyphenylacetic acid (4-HPAA), 3,4-dihydroxybenzoic acid (protocatechuic acid, PCA), 4-hydroxybenzoic acid (4-HBA), benzoic acid (BA), 3-hydroxyphenylpropionic acid (3-HPPA), phloroglucinol, 3,4-dihydroxytoluene (3,4-DHT), 3-hydroxyhippuric acid (3-HHA), 4-hydroxyhippuric acid (4-HHA), and hippuric acid (HA) were detected in urinary or fecal excretion of humans or rats with feeding administration, in rumen fluid of cows after rutin ingestion, or in co-fermentation of flavonol in vitro with human fecal extract or selected bacterial strains. ,,, The degradation pathways of quercetin in vivo are presented in Figure .…”
Section: In Vivo Metabolic Fate and Metabolites Of Quercetin As An Ex...mentioning
confidence: 99%